2015
DOI: 10.1099/mic.0.083493-0
|View full text |Cite
|
Sign up to set email alerts
|

Serological characterization of the enterobacterial common antigen substitution of the lipopolysaccharide of Yersinia enterocolitica O : 3

Abstract: Enterobacterial common antigen (ECA) is a polysaccharide present in all members of Enterobacteriaceae anchored either via phosphatidylglycerol (PG) or LPS to the outer leaflet of the outer membrane (ECA PG and ECA LPS , respectively). Only the latter form is ECAimmunogenic. We previously demonstrated that Yersinia enterocolitica O : 3 and its rough (Ospecific polysaccharide-negative) mutants were ECA-immunogenic, suggesting that they contained ECA LPS ; however, it was not known which part of the LPS core regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…pTM100‐CRISPR was electroporated into E. coli strain ω7249. pTM100‐waaF (Noszczynska et al ., ) was used as spacer‐free control plasmid in mobilization experiments.…”
Section: Methodsmentioning
confidence: 99%
“…pTM100‐CRISPR was electroporated into E. coli strain ω7249. pTM100‐waaF (Noszczynska et al ., ) was used as spacer‐free control plasmid in mobilization experiments.…”
Section: Methodsmentioning
confidence: 99%
“…MBL was originally described as the murine Ra-reactive factor (RaRF), activating the complement cascade by interaction with Salmonella LPS of Ra type but not with the smooth or Re chemotypes (Ihara et al, 1982). Later, MBL has been demonstrated to react with OPS or YeO3-c-R1 waaF::cat-Mu, clmR Rd2 (LA-3/8IC) c Noszczynska et al (2015) a All the Y. enterocolitica strains are ECA-positive, except the ones from which the ECA-gene cluster has been deleted. b The OC hexasaccharide is truncated by two glucose residues.…”
Section: Introductionmentioning
confidence: 98%
“…The exact linkage of ECA LPS to the LA-IC (Fig. 1B) is not determined yet although it was indirectly shown to be the Kdo region (Noszczynska et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…E. coli O14 was proven later on to be rough and synthesize LOS characterized by the R4 core chemotype [ 13 , 14 ]. Further studies demonstrated that ECA LPS -dependent immunogenicity generally was limited only to a few rough enterobacteria with complete core OS, such as, for example, E. coli R1, R4, and K-12 [ 15 ], E. coli R2 and R3 [ 15 , 16 , 17 ], Proteus mirabilis [ 18 ], S. sonnei phase II [ 19 ], and Yersinia enterocolitica O:3 and O:9 [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%